A prospective case of postherpetic itch monitored by quantitative sensory testing for 1 year while undergoing 8% topical capsaicin treatments. Issue 3 (December 2017) - Andersen, Hjalte H.; Arendt-Nielsen, Lars; Yosipovitch, Gil; Elberling, Jesper
Abstract : Following reactivation of a latent ganglionic varicella zoster virus and skin eruption in the corresponding dermatome(s) ∼20% of patients develop chronic postherpetic neuralgia. A subset of these patients develop severe and often intractable chronic postherpetic itch in the affected area. However, this is rarely studied and little is known about its epidemiology, pathogenesis, and management. In this case study we followed a patient with moderate to severe chronic postherpetic itch characterized by pure itch sensation, using standardized quantitative sensory testing and observed a profound loss-of-function for C-fibers, Aδ-fibers, and Aβ-fibers within the affected area. The testing was conducted before, during, and after 8% topical capsaicin treatments applied in 4 cycles (3 months apart) over the course of ∼1 year. During this period the hypoesthesia gradually normalized, but heat hypoalgesia remained unchanged. The 8% topical capsaicin had a good and long lasting antipruritic effect eventually resulting in complete resolution of the itch in parallel with partial recovery of initial hypoesthesia, particularly for warmth and cold detection, likely unrelated to the treatments.